Tactile print: identification labels for prints and colors of clothing for the visually impaired (ModaPalavra e-periódico, 2021)
The choice of clothes is part of the daily lives of most users. Graphic elements and colors are visual aspects that personalize items and identify styles. For the visually impaired, clothing choices and identification are not made independent. So, as an interface to help identify the patterns and colors of clothing, this study proposes to develop tactile labels with elements of surface design for the visually impaired, meeting their needs during shopping and daily use. Through an exploratory, descriptive and qualitative study, interviews were conducted with the target audience at the Associação Catarinense de Integração ao Cego - ACIC, as an analysis of the interaction of the visually impaired with clothing. The design of the prototypes was carried out in partnership with Tecnoblu,  company of clothing customization products of Santa Catarina, using as a methodology the Guidance of Development Projects - GDP.
Keywords: tactile labels; visually impaired; surface design; visually impaired people